Patterns of Pelagic Fish Diversity in Floodplain Lakes of Whitewater and Blackwater Drainage Systems Within the Central Amazon River Basin of Brazil - Siqueira-Souza, Flávia K.; Hurd, Lawrence E.; Yamamoto, Kedma C.; Soares, Maria Gercilia M.; Cooper, Gregory J.; Kahn, James R.; Freitas, Carlos E. C. (Frontiers in Ecology and Evolution, 2021)
The Amazon River Basin, one of the world’s most threatened ecosystems, has an enormous diversity of fish species, a result of temporally and spatially complex habitat containing biogeochemically different river systems. The annual hydrologic cycle results in floodplain lakes during low water and inundates forests during high water, exposing fish to different resources and environmental conditions. The two principal river systems in the central Brazilian Amazon are blackwater, with nutrient-poor acidic water, and nutrient-rich whitewater. Although species-rich, the Amazon Basin is data-poor in terms of comparative studies on a regional scale. We analyzed data sets from independent sampling studies of pelagic fish in16 floodplain lakes, nine whitewater (Rio Solimões) and seven blackwater (Rio Negro), in the central Amazon Basin of Brazil. Our findings suggest striking similarities in pelagic fish diversity patterns. Species richness was virtually equal (165 in whitewater and 168 in blackwater), Both species richness, and number of migratory species, per lake increased toward the confluence of the rivers in both systems in our study. The proportion of unique species was also similar in whitewater lakes and blackwater (41% and 43%, respectively), boosting total regional richness to 237 species. However, species composition in whitewater lakes was more homogenous (lower β diversity), and species composition was associated with conductivity and pH in whitewater, but with dissolved oxygen and transparency in blackwater. Therefore, regional fish diversity cannot be represented by sampling one lake or even one drainage system, but must include multiple lakes from both systems. These two systems may differ in sensitivity to anthropogenic stressors such as damming and deforestation.